Rumble fish - Hinton, S. E (New York : Dell Pub., 1989)
A junior high school boy idolizes his older brother, the coolest, toughest guy in the nieghborhood, and wants to be just like him
"Laurel-leaf contemporary fiction"--Cover
Keywords: Brothers and sisters -- Juvenile fiction; City and town life -- Juvenile fiction; Social problems -- Juvenile fiction